CORE CURRICULUM MANAGEMENT BASED AUTHENTIC INSTRUCTIONAL MODEL - Caraka Putra Bhakti; Fuad Aminur Rahman; Muhammad Alfarizqi Nizamuddin Ghiffari (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2018)
The purpose of this paper is as a reference model of core curriculum management services with the instructional authentic model.  core curriculums are one of the most important services to be delivered to today's students. core curriculums aim to optimize the potential of today's students. Optimization of student potential can be realized if service, implementation and service evaluation can be done by school counselor optimally. This is closely related to management, which in general management is the ability to manage things to achieve certain goals. From this, the core curriculum which as part of the education needs to be resolved or has good management. Obviously, manage core curriculum need to attend to appropriate model and development of students. In core curriculum, Management model authentic instructional model. This model is a pedagogical approach which puts in the context of the future. From this model, the core curriculums provided to students oriented toward students and up to date. This will help school counselors continue to innovate and develop core curriculums applied to students. It is hoped that through this model, school counselors can plan and develop and become an evaluation material for themselves in developing a core curriculum.